(untitled) (Estudios de Historia de España, 2017)
Before libraries and reference archives, essential for the richness of their materials, there are smaller and virtually unknown documental repositories, such as the Library of the Centro Argentino de Estudios Históricos “Claudio Sanchez Albornoz” current headquarters of the Seminario de Edición y Crítica Textual “Germán Orduna” that preserves part of the library of that historian. An examination of the volumes that are part of it reveals friendships, professional relationships and modes of reading and commenting on whom was the president of the Spanish Republic in exile and one of the founders of historical studies on the Middle Ages in Argentine